General processes, rather than "goals," explain imitation errors. - Bird, G; Brindley, R; Leighton, J; Heyes, C (2007)
The goal-directed theory of imitation (GOADI) states that copying of action outcomes (e.g., turning a light switch) takes priority over imitation of the means by which those outcomes are achieved (e.g., choice of effector or grip). The object < effector < grip error pattern in the pen-and-cups task provides strong support for GOADI. Experiment 1 replicated this effect using video stimuli. Experiment 2 showed that shifting the color cue from objects to effectors makes imitation of effector selection more accurate than imitation of object and grip selection. Experiment 3 replicated this result when participants were required to describe actions. Experiment 4 indicated that, when participants are imitating and describing actions, enhancing grip discriminability makes grip selection the most accurately executed component of the task. Consistent with theories that hypothesize that imitation relies on task-general mechanisms (e.g., the associative sequence learning model, ideomotor theory), these findings suggest that imitation is no more or less goal directed than other tasks involving action observation.